Assessment of competences: professioh nal and university environment - Z. . Yakimova; V. . Nikolaeva (Высшее образование в России)
In this paper the authors have analyzed the tools for assessing competencies in higher school and professional environment. The possibility of borrowing and adaptation of the toolsof professional environment in modern educational process were considered. Assessment toolsfor skills programs as close monitoring of progress and interim assessment of students in terms of their future careers were analyzed.